Developments in immunofluorescence: the need for standardization - Johnson, G. D. (1967)
Difficulties experienced by the newcomer to the fluorescent antibody staining method largely arise from two causes: (1) the many modifications in the procedure which have been suggested over the last decade; (2) the variability of the basic reagent, fluorescent conjugate, in terms of potency and specificity. The ensuing problem of non-reproducibility is clearly an important factor for clinical laboratories now faced with increasing demands for routine tests involving immunofluorescence. In this paper a simple approach to standardization is described which, if adopted, would lead to a more efficient use of the method.